Influence of nano-sized fumed silica on physicochemical and electrochemical properties of cellulose derivatives-ionic liquid biopolymer electrolytes - Rani, Mohd Saiful Asmal; Ahmad, Azizan; Mohamed, Nor Sabirin (Springer Verlag (Germany), 2018)
Nanocomposite biopolymer electrolyte was prepared by solution-casting technique. Carboxymethyl cellulose from kenaf bast fibre, ammonium acetate, (1-butyl)trimethyl ammonium bis(trifluoromethylsulfonyl)imide ionic liquid and silica nanofiller was used to prepare the biopolymer electrolyte samples. The films were characterized by Fourier transform infrared spectroscopy, electrochemical impedance spectroscopy, scanning electron microscopy, transference number measurement and linear sweep voltammetry. The interactions of doping salt, ionic liquid and inorganic nanofiller with the host biopolymer were confirmed by FTIR study. The highest conductivity achieved was 8.63 × 10−3 S cm−1 by the incorporation of 1 wt% of SiO2 at ambient temperature. The electrochemical stability of the highest conducting sample was stable up to 3.4 V, and the ion transference number in the film was 0.99.